Effects of hemodialysis on serum fetuin-A levels - Roman Safranek; Michaela Kubisova; Lydia Habanova; Petr Moucka; Jakub Visek; Marta Kalousova; Miroslav Merta; Lubos Sobotka; Sylvie Dusilova Sulkova (The Korean Society of Nephrology, 2012)
Fetuin-A is a calcification inhibitor, negative acute phase response marker and cardiovascular mortality predictor in hemodialysis patients. Low levels of fetuin-A are associated with malnutrition, inflammation, decreased bone mass density, low-turnover bone and use of high calcium concentration dialysate. Hemodialysis procedure (HD) has been shown to decrease fetuin-A levels by 20%, probably due to HD-induced inflammation or acute changes in calcium metabolism. The aim of our study was to investigate effects of HD on serum fetuin-A levels. Forty clinically and hemodynamically stable hemodialysis patients (21 females, 68 (38-85) years) underwent routine bicarbonate hemodialysis or hemodiafiltration with polysulfone dialyzer. On consecutive HD dialysis solution with different calcium concentration with/without citric acid was used to assess influence of calcium shifts and parathyroid activity on fetuin-A changes during HD. All other parameters of HD were kept constant. Serum fetuin-A, calcium, phosphorus, iPTH, CRP and other biochemical parameters were measured before and after each HD. Our data show that predialysis serum fetuin-A levels have positive correlation with iPTH levels (p<0.05) and tendency to decrease with higher CRP levels. There was no change in fetuin-A levels during HD: 206 (167.1; 231.9) ug/ml before and 208.9 (170.3; 246.3) ug/ml after HD; respectively. When corrected for haemoconcentration, decrease in fetuin-A was only 2.8% (p<0.05). There was also no difference between effect of hemodialysis and hemodia-filtration procedure. The use of different calcium dialysate concentrations had distinct effect on iPTH levels during and after HD, however, we observed no associated changes in fetuin-A levels. The use of dialysate solution with citric acid had no effect on fetuin-A levels. In conclusion, standard bicarbonate HD with polysulfone dialyser and ultrapure dialysate induces only minor changes in fetuin-A and no changes in hsCRP levels. iPTH levels correlate positively with predialysis fetuin-A, but distinct acute changes in iPTH secretion induced by different dialysate calcium concentrations have no effect on serum fetuin-A levels after a single HD.